2014
DOI: 10.1371/journal.pone.0101744
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alumina Binder Content on Catalytic Performance of Ni/HZSM-5 for Hydrodeoxygenation of Cyclohexanone

Abstract: The influence of the amount of alumina binders on the catalytic performance of Ni/HZSM-5 for hydrodeoxygenation of cyclohexanone was investigated in a fixed-bed reactor. N2 sorption, X-ray diffraction, H2-chemisorption and temperature-programmed desorption of ammonia were used to characterize the catalysts. It can be observed that the Ni/HZSM-5 catalyst bound with 30 wt.% alumina binder exhibited the best catalytic performance. The high catalytic performance may be due to relatively good Ni metal dispersion, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…In fact, high hydrogen partial pressure leads to the saturation of aromatic intermediates through the hydrogenation reaction and thus prevents the generation of aromatics such as benzene in this reaction condition. This is in accordance with the observations of previous studies . Runnebaum et al observed the presence of aromatics at 573 K and 1.4 bar of hydrogen partial pressure.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, high hydrogen partial pressure leads to the saturation of aromatic intermediates through the hydrogenation reaction and thus prevents the generation of aromatics such as benzene in this reaction condition. This is in accordance with the observations of previous studies . Runnebaum et al observed the presence of aromatics at 573 K and 1.4 bar of hydrogen partial pressure.…”
Section: Resultssupporting
confidence: 93%
“…Based on the obtained results, the reaction networks sketched in Figure are considered for the HDO of cyclohexanone in the presence of pure hydrogen and syngas at 300°C and 20 bar of total pressure. This reaction network is in accordance with the observations of previous studies . The hydrogenation reaction leading to the formation of cyclohexanol is followed by the dehydration reaction, which results in the generation of cyclohexene.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The catalyst pellet appeared to be the best formulation over catalyst extrudates ( Figure 5). A new concept appeared along with the study of Kong et al [14] devoted to the inter-crystalline mesoporosity generation by the addition of binders. They observed an increase of mesopores created by intercrystalline voids of alumina crystallites leading to a better performance of Ni/ZSM-5 zeolite in the hydrodeoxygenation of cyclohexanone.…”
Section: Silica and Alumina Bindersmentioning
confidence: 99%
“…3. Typical peaks of HZSM-5 (23-24°) were maintained in all catalysts, indicating that the framework of HZSM-5 remained constant after nickel loading [41]. The peaks of NiO (37.2°, 43.3°) were detected in the diffraction patterns of 7.64 % NiO/HZSM-5 and 15.27 % NiO/HZSM-5.…”
Section: Characterization Of the Catalystsmentioning
confidence: 78%